PENGARUH KONSENTRASI SUSU SKIM DAN LAMA PENYIMPANAN TERHADAP KADAR ASAM LAKTAT DAN pH YOGHURT - Marlina, Lusi; Kristiani, Mega (Jurnal TEDC; Vol 20 No 1 (2026): JURNAL TEDC, 2026)
Yoghurt is a fermented dairy product characterized by an acidic taste and low pH resulting from lactic acid bacteria activity. The chemical characteristics of yoghurt are influenced by raw material formulation and storage conditions. This study aimed to analyze the effect of skim milk concentration and storage duration on lactic acid content and yoghurt pH. The study was conducted experimentally using skim milk concentrations of 3%, 4%, and 5% with storage periods of 1, 7, and 14 days under refrigerated conditions. Lactic acid content was analyzed using alkalimetric titration, while pH was measured using a pH meter. The results showed that increasing skim milk concentration and storage duration increased lactic acid content and decreased yoghurt pH during controlled cold storage.